PUBLIC RELATIONS IN PRIVATE UNIVERSITIES IN CENTRAL JAVA: CREATING INNOVATION TO ATTRACT STUDENTS’ INTEREST - Wijaya, Lina Sinatra (Institute of Research and Community Outreach - Petra Christian University, 2015)
Nowadays, The competition among private universities especially in Central Java is getting tougher. Each higher education tries to achieve their goal which is generally to attract students’ interest which will influence the higher student intake in each academic year. This study tried to investigate the creative innovation created by the private university to attract students’ interest which will give influence in students intake. This study employed interview and literature study for data collections. The data were then analyzed qualitatively to answer the posed research questions. This study involved 8 private universities in Central Java. The result of this study showed that the public relations role in private university is as communication technician, expert prescriber, communication facilitator and also as problem solver facilitator. Besides that, the public relations practitioners in private university have tried to create innovation program for attracting students’ interest. This innovation gave positive impact on the intake of the private university at least 5 % - 20%.